Should Conciliation Boards be Abolished? (Relations industrielles / Industrial Relations, 1952)
SommaireShould Conciliation Boards be abolished? This is an interesting question raised up in the contributed editorial of the 1952 winter issue of "Public affairs" and presented in the following way.